Controle e avaliação do planejamento estratégico no Instituto Federal de Educação, Ciência e Tecnologia Farroupilha - Reis, Diego Brenner dos (2019)
This research aimed to identify how the control and the evaluation about the execution of the Federal Institute of Education, Science and Technology Farroupilha strategic planning support the managers in the decision-making process. Regarding to methodological procedures this research is characterized as qualitative, applied, exploratory and case study. The investigation involved the institutional documents analysis, semi-structured interviews with opened questions and consultation of legislation. Responded to the interviews the servants who are managers at the Rectory and campi in the institution. The results demonstrated that the elaboration of the strategic planning of the Federal Institute of Education, Science and Technology Farroupilha is formalized in the Institutional Development Plan according to the Ministry of Education. The control and the evaluation of the strategic planning occur through monitoring of information systems such as the Integrated Management System, the Federal Government's Integrated Financial Management System, the National Information System for Vocational and Technological Education, the Nilo Peçanha Platform and control spreadsheets. These resources are used to obtain and organize data and reports that are analyzed and converted into information that supports managers in decision-making process. Thus, the main conclusion of this research indicates that the exploration of the institutional results linked to planning and provided by the control tools is taken as a reference in the decision-making process and it has been applied by the managers to base their actions and direct strategic actions aiming at the intended results. Finally, it evidences the relationship between the control and the evaluation of the strategic planning and the decision-making process, since both processes feeds off one another with data and information and, in many cases, it shares the same tools.